Factors affect attitude towards using e-Caruman of Employees Provident Fund / Nur Hanani Bohari - Bohari, Nur Hanani (Faculty of Business and Management, 2016)
The technology acceptance model has identified the role of the perceived usefulness and perceived ease-of-use constructs in the information technology adoption process. Whereas past research has been valuable in explaining how such beliefs lead to system use such as online banking, online shopping, e-government and others support system. Therefor this study is to examine what extend attitude using e-caruman towards employers affected with the Technology acceptance model factors. In completing this research, cluster sampling was used. The sample for this survey was drawn from 220 employers who have i-Akaun and make payment at EPF counter. The questionnaires were distributed during peak hours within 2 weeks by researcher. There are three conceptual factors which are perceived ease of use, perceived usefulness and perceived web security has been analysed. The study revealed that perceived usefulness standout as main influential factors towards attitude using the e-caruman service.